ChemInform Abstract: Water Mediated Eco‐Friendly Green Protocol for One‐Pot Synthesis of α‐Aminophosphonates at Ambient Conditions. Issue 47 (6th November 2014) - Mandha, Santhosh Reddy; Alla, Manjula; Bommena, Vittal Rao
Abstract The title compounds (IV) are simply obtained by reaction of various aldehydes, amines, and trimethyl phosphite under totally solvent‐free and catalyst‐free conditions.